2020
DOI: 10.1371/journal.pntd.0008826
|View full text |Cite
|
Sign up to set email alerts
|

The awareness of neglected tropical diseases in a sample of medical and nursing students in Cairo University, Egypt: A cross-sectional study

Abstract: Neglected tropical diseases (NTDs) are a group of chronic diseases affecting 1.2 billion people worldwide, with more burden in the developing communities. Improving awareness about NTDs is a powerful affordable long-term intervention for infection control. In literature, there is a limited number of studies in the developing countries assessing the awareness of healthcare providers regarding these diseases. The present study aimed at assessing the awareness of a sample of Cairo University medical and nursing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
4
4
0
1
Order By: Relevance
“…This disparity could be due to poor packaging of messages during delivery of health education for schistosomiasis and STH. These nding are similar to studies done in Nigeria, Egypt, Cameroon, Papua New Guinea, Turkey and Philippines which demonstrated that despite implementation of numerous activities towards the control of NTDs, there is little sensitization of the general public in order to increase awareness of the diseases [50][51][52][53][54][55].…”
Section: Community Participation In Mda Deliverysupporting
confidence: 86%
See 1 more Smart Citation
“…This disparity could be due to poor packaging of messages during delivery of health education for schistosomiasis and STH. These nding are similar to studies done in Nigeria, Egypt, Cameroon, Papua New Guinea, Turkey and Philippines which demonstrated that despite implementation of numerous activities towards the control of NTDs, there is little sensitization of the general public in order to increase awareness of the diseases [50][51][52][53][54][55].…”
Section: Community Participation In Mda Deliverysupporting
confidence: 86%
“…The need to engage the public in NTD prevention and control activities has become imperative in the context of morbidity reduction through MDA delivery and community participation [50]. An increase in the awareness of community members regarding schistosomiasis and STH is important for them to play a central role in the prevention and control of these diseases [51]. This study has found that knowledge levels about schistosomiasis and STH varied disproportionately between survey respondents according to aspects asked about and district.…”
Section: Community Participation In Mda Deliverymentioning
confidence: 93%
“…This may have challenged the people in fully understanding these diseases, and for them to appreciate the importance of MDA and other control measures. The findings agree with other studies done in Malawi [7], Philippines [27], Nigeria [28], Egypt [29], Cameroon [30], Papua New Guinea [31] and Turkey [32] demonstrating that despite implementation of numerous activities towards the control of NTDs, there was little sensitization of the general public in order to increase awareness of the diseases. The need to engage the public in schistosomiasis and STH prevention and control activities has become imperative in the context of morbidity reduction through MDA delivery and community participation.…”
Section: Discussionsupporting
confidence: 90%
“…The need to engage the public in NTD prevention and control activities has become imperative in the context of morbidity reduction through MDA delivery and community participation [ 51 ]. An increase in the awareness of community members regarding schistosomiasis and STH is important for them to understand these diseases and to play a central role in their prevention and control [ 52 ]. This study has found that knowledge levels about schistosomiasis and STH varied disproportionately among survey respondents according to aspects asked about and district.…”
Section: Discussionmentioning
confidence: 99%